Teaching Science Books Based on Bakpia Local-Potential to Improve Students’ Critical Thinking and Communication Skills - Nisa, Wilda Muhimmatun; Wilujeng, Insih (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2020)
This study is aimed at determining the effectiveness of the use of a science textbook integrated with the local potentials of bakpia in improving the critical thinking and communication skills of the junior high school students. The study was a quasi-experiment with a pretest-posttest control group research design. The experiment and control groups were taken by cluster random sampling by considering the location of the school, which is within proximity of the local potentials in question. The study was conducted in the 7th grade, at one of the junior high schools in Yogyakarta, both for the experiment and control classes. The research instruments were an open-reasoned multiple-choice test and observation sheets to obtain data on students’ critical thinking skills and communication skills. Data analysis was done by the Manova difference test assisted by the SPSS 2.0 computer program with a significance value lower than 0.05. Results showed that the value of the partial Eta squared from the Manova test was 0.981, indicating that the effectiveness of the science textbook integrated with the bakpia local potentials to improve students’ critical thinking and communication skills was in the “high” category. The test of between subject effects of the Manova test showed a significant value of students’ critical thinking and communication skills of less than 0.05. Therefore, it can be said that the science textbook was effective in increasing students’ critical thinking and communication skills, simultaneously. A limitation to the study can be in the fact that the study is not conducted directly in the bakpia factory and that it involves only 60 subjects for both the experiment and control groups. The integrated textbook of bakpia local potentials can be used as a reference for future researchers with other local potentials. The local potential integrated book can also become an alternative-learning mode, e.g.: based on STEM, with materials suitable for local potentials in other regions.